2019
DOI: 10.1080/1359432x.2019.1576633
|View full text |Cite
|
Sign up to set email alerts
|

Beyond one work day? A daily diary study on causal and reverse effects between experienced workplace incivility and behaving rude towards others

Abstract: Van Dick (2019) Beyond one work day? A daily diary study on causal and reverse effects between experienced workplace incivility and behaving rude towards others,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…The third hypothesis of the present study proposed that WPI intervenes in the negative association of DT and OCB. Findings of this study proved H3, which explains that dark personality holder individuals behave uncivil at the workplace with their supervisors, peers, and subordinates when they feel the threat to their ego from the environment of the organization, that resultantly reduce positive outcomes i.e., OCB (Abrar et al, 2014;Liu et al, 2019;Schilpzand et al, 2016;Taylor et al, 2012;Vahle-Hinz, Baethge, & Van Dick, 2019). Furthermore, by using the lens of ECT (Victor & Cullen, 1987, 1988, the fourth hypothesis of this study proposes that the ethical climate of the organization diminishes the intensity of negative personality and their uncivil behaviors.…”
Section: Discussionmentioning
confidence: 52%
“…The third hypothesis of the present study proposed that WPI intervenes in the negative association of DT and OCB. Findings of this study proved H3, which explains that dark personality holder individuals behave uncivil at the workplace with their supervisors, peers, and subordinates when they feel the threat to their ego from the environment of the organization, that resultantly reduce positive outcomes i.e., OCB (Abrar et al, 2014;Liu et al, 2019;Schilpzand et al, 2016;Taylor et al, 2012;Vahle-Hinz, Baethge, & Van Dick, 2019). Furthermore, by using the lens of ECT (Victor & Cullen, 1987, 1988, the fourth hypothesis of this study proposes that the ethical climate of the organization diminishes the intensity of negative personality and their uncivil behaviors.…”
Section: Discussionmentioning
confidence: 52%
“…Further, evidence showed that only four studies (three of them in United States and one in UK) utilized experiment design (4.3%). Interestingly, only more recently diary surveys started to be used by researchers (Nicholson and Griffin, 2017;Vahle-Hinz et al, 2019). The two studies under such a denomination were conducted in Australia and German.…”
Section: Collection Methodsmentioning
confidence: 99%
“…Accordingly, the social interactionist model (Andersson and Pearson, 1999) suggests that targets might respond to experienced interpersonal conflict by enacting negative interpersonal behaviors themselves. Yet, moving beyond the assumption of direct reciprocity, the social interactionist model suggests that, in an attempt to establish justice or to defend their self-worth, targets might pay back negative acts of others not only by behaving negatively toward the offender but also by redirecting their negative reaction toward others (i.e., displaced retaliation; e.g., Rosen et al, 2016;Vahle-Hinz et al, 2019). Indeed, experiencing negative treatment, conflicts, or interactional injustice (Ambrose et al, 2002) elicits global negative interpersonal responses including low general willingness to help coworkers (e.g., Chiaburu and Harrison, 2008) or to exchange knowledge (Chen, 2011), and high overall, generalized knowledge hiding (Jahanzeb et al, 2019;Khalid et al, 2018).…”
Section: Interpersonal Conflict With Coworkers As An Antecedent Of Comentioning
confidence: 99%